Development Of Bacterial Culture For Odour Control - Chin, Siat Pei (2011)
Volatile fatty acids particularly butyric acid is known as the major component of odour, associated with livestock farming, agricultural activities and wastewater treatment system. Thirteen butyric acid-degrading bacteria were isolated from the rivers and cow farm in Malaysia. Screening with specific growth rates and butyric acid degradation rates had selected four strains of highest values. These four bacteria were identified as Cupriavidus sp. strain B3, Burkholderia sp. strain C2, Acinetobacter sp. strain C4 and Cupriavidus sp. strain C5. Among the four, Acinetobacter sp. strain C4 showed the highest values of specific growth rate at (0.321±0.002) h-1, and degradation rate at 54 ppm butyric acid/h.